A CLINICAL STUDY OF THE METHOD OF EARLY DIAGNOSIS OF POSTINFARCTION CARDIOSCLEROSIS - Kodirova G.I; Askarov B. (Scholar Express Journals, 2024)
Recently, the issue of early diagnosis of coronary heart disease (CHD) remains the most urgent task of cardiology. The gas analytical method for the analysis of exhaled air (EA) is a new approach to solving this problem [1,5,11]
Keywords: heart disease; ischemic myocardial zones; kinetic parameters